2018
DOI: 10.1038/s41590-017-0024-8
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: A gammaherpesvirus provides protection against allergic asthma by inducing the replacement of resident alveolar macrophages with regulatory monocytes

Abstract: In the version of this article initially published, the accession code for the RNA-seq data set deposited in the NCBI public repository Sequence Read Archive was missing from the 'Data availability' subsection of the Methods section. The accession code is SRP125477.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…with murid herpesvirus 4 (MuHV-4) in BALB/c mice 35 or influenza in C57/BL6 mice, 36 resident AMs are rapidly depleted after infection, potentially providing a new niche for recruited monocytederived M𝜙s. Machiels and colleagues 35 showed that at day 8 after MuHV-4 infection, a large number of monocytes from BM arrived in the alveolar space, and eventually replaced resident AMs, remaining in this niche for weeks. In another study, acute inflammation caused by LPS, results in remarkable transcriptional differences between resident and monocyte-derived AMs in cell proliferation, inflammatory response, and metabolism.…”
Section: Key Roles Of Ams and Imsmentioning
confidence: 99%
See 1 more Smart Citation
“…with murid herpesvirus 4 (MuHV-4) in BALB/c mice 35 or influenza in C57/BL6 mice, 36 resident AMs are rapidly depleted after infection, potentially providing a new niche for recruited monocytederived M𝜙s. Machiels and colleagues 35 showed that at day 8 after MuHV-4 infection, a large number of monocytes from BM arrived in the alveolar space, and eventually replaced resident AMs, remaining in this niche for weeks. In another study, acute inflammation caused by LPS, results in remarkable transcriptional differences between resident and monocyte-derived AMs in cell proliferation, inflammatory response, and metabolism.…”
Section: Key Roles Of Ams and Imsmentioning
confidence: 99%
“…Siglec‐F, CD169, and CD206, are present at higher levels on murine resident AMs while monocyte‐derived AMs express higher levels of Ly6C 30,33,34 and the death receptor Fas 30,33 . During infection, e.g.,, with murid herpesvirus 4 (MuHV‐4) in BALB/c mice 35 or influenza in C57/BL6 mice, 36 resident AMs are rapidly depleted after infection, potentially providing a new niche for recruited monocyte‐derived Mϕs. Machiels and colleagues 35 showed that at day 8 after MuHV‐4 infection, a large number of monocytes from BM arrived in the alveolar space, and eventually replaced resident AMs, remaining in this niche for weeks.…”
Section: Introductionmentioning
confidence: 99%
“…We know alveolar macrophages are critical effector cells in initiating and maintaining pulmonary inflammation, as well as termination and resolution of pulmonary inflammation during acute lung injury (ALI) (Beck-Schimmer et al, 2005;Herold et al, 2011). Therefore, to determine if the altered gene expression profiles we observed following ALI in the BAL were due to lincRNA-Cox2 expression in alveolar macrophages we cultured primary alveolar macrophages from our WT and lincRNA-Cox2 mutant mice and measured cytokine and chemokine expression (Machiels et al, 2017;Nayak et al, 2018;Robinson et al, 2021). Excitingly, we found decreased expression of Il6, Ccl3 and Ccl4 and increased expression of Ccl5 in the lincRNA-Cox2 mutant alveolar macrophages (Figure 6 D-G).…”
Section: Discussionmentioning
confidence: 99%